2004
DOI: 10.1186/1477-7827-2-25
|View full text |Cite
|
Sign up to set email alerts
|

Expression of connexins in human preimplantation embryos in vitro

Abstract: Intercellular communication via gap junctions is required to coordinate developmental processes in the mammalian embryo. We have investigated if the connexin (Cx) isoforms known to form gap junctions in rodent preimplantation embryos are also expressed in human embryos, with the aim of identifying species differences in communication patterns in early development. Using a combination of polyA PCR and immunocytochemistry we have assessed the expression of Cx26, Cx31, Cx32, Cx40, Cx43 and Cx45 which are thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Gerbaud et al found that Cx43 accelerated trophoblast fusion process by activating protein kinase A (PKA)-dependent phosphorylation [ 35 ]. Cx43 is an important component for gap junction formation in human preimplantation embryos [ 36 ]. Rmanathal et al found that Cx43 played critical role in controlling the paracrine secretions of stromal cells under decidualization, which may alter the proliferation and migration of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gerbaud et al found that Cx43 accelerated trophoblast fusion process by activating protein kinase A (PKA)-dependent phosphorylation [ 35 ]. Cx43 is an important component for gap junction formation in human preimplantation embryos [ 36 ]. Rmanathal et al found that Cx43 played critical role in controlling the paracrine secretions of stromal cells under decidualization, which may alter the proliferation and migration of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Xenopus Cx31 and Cx43.4, the orthologues of hCx31 and Cx45, are expressed in both oocytes and early embryos (41). Cx31 and Cx45 transcripts occur in the pronucleate to four cell stage during human embryogenesis (42). Thus, heterotypic coupling between Cx31 and Cx45 may be important in early stages of development.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 is one of the most important proteins present in the gap junction channels located between mammalian ventricular muscle cells ( 49 ). It serves an important role in cardiac development, normal cardiac electrical activity, heart diastolic movement and the differentiation of stem cells to myocardial cells ( 50 ).…”
Section: Discussionmentioning
confidence: 99%